STRATEGIC MODEL FOR SUSTAINABLE DEVELOPMENT OF SMART CITIES - Chipriyanov, Mihail (E-Journal VFU, 2026)
This study introduces an original strategic model for the development of smart cities in Bulgaria, titled Smart Urban Intelligence Strategist (SUIS). The model proposes a transition from fragmented management to a holistic approach through the establishment of an integrated digital ecosystem. Particular emphasis is placed on the Smart Financing module, which leverages blockchain technology and a Sustainable Convergence Coefficient (SCC) to measure the synergy between economic performance and ESG (Environmental, Social, and Governance) indicators. This research provides a robust scientific framework for achieving adaptability and long-term sustainability within the urban environment.